2020
DOI: 10.4209/aaqr.2020.02.0074
|View full text |Cite
|
Sign up to set email alerts
|

Urban Air Pollutant from Motor Vehicle Emissions in Kuala Lumpur, Malaysia

Abstract: The increasing amount of motor vehicles that emit pollutants are contributing significantly to urban air pollution, be it in industrial or developing countries. This study investigates the emission of particulate matter (PM10) from exhaust and non-exhaust sources and gaseous pollutants, such as carbon monoxide (CO) and nitrogen oxide (NOx) from several different classes of motor vehicles in the tropical city of Kuala Lumpur. Air pollutants from fuel consumption were obtained from emission factors, while non-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Despite the environmental laws enforced in Malaysia, the question remains on the effectiveness of environmental law enforcement as air pollution remains a pertinent issue in Malaysia. Shafie & Mahmud (2020), p. 2,793) reported that motor vehicles and traffic are the dominant causes of urban air pollution in Malaysia. This situation is also supported by Chin et al (2019), p. 15) that reported that while 65 percent of the study sample are aware of health hazards of air pollutants from vehicles, they rejected the idea of using public transportation.…”
Section: A Motor Vehicles and Land Transportationmentioning
confidence: 99%
“…Despite the environmental laws enforced in Malaysia, the question remains on the effectiveness of environmental law enforcement as air pollution remains a pertinent issue in Malaysia. Shafie & Mahmud (2020), p. 2,793) reported that motor vehicles and traffic are the dominant causes of urban air pollution in Malaysia. This situation is also supported by Chin et al (2019), p. 15) that reported that while 65 percent of the study sample are aware of health hazards of air pollutants from vehicles, they rejected the idea of using public transportation.…”
Section: A Motor Vehicles and Land Transportationmentioning
confidence: 99%
“…According to the total weight of vehicles, Chinese motor vehicles can be divided into four categories: light, medium, heavy and motorcycle. Motor vehicle exhaust contains more than 200 kinds of compounds (Zhu et al, 2008;Mohd Shafie and Mahmud, 2020;González et al, 2020), the main pollutants are CO, HC, NOx and lead compounds, sulfide, smoke, oil mist, etc. Among the pollutants of motor vehicle exhaust, CO makes the largest contribution to motor vehicle exhaust.…”
Section: Introductionmentioning
confidence: 99%
“…These harmful gases diffuse into the air will cause air pollution and harm the human body. In 2016, on-road vehicles accounted for about 39% and 20% of total NO2 and CO emissions in the European Union (EU), and it is found those passenger vehicles are the major cause of NO2 and CO emissions from road transportation (Mohd Shafie and Mahmud, 2020;Iqbal et al, 2022). It has been reported that for every kilogram of gasoline burned by the automobile engine (Deng, 2006;Zhao et al, 2021), 15 kilograms of fresh air will be consumed, and 150-200 grams of carbon monoxide, 4-8 grams of hydrocarbons, 4-20 grams of nitrogen oxide and other pollutants will be emitted at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Malaysia, like many upper-middle-income countries, has seen rapid growth in population, urbanisation, and economic output, so the effect of air pollution and climate change on children has been of growing concern [23]. Local air quality is a function of the vehicular traffic [24], industrial activity [25] and haze pollution caused by biomass emissions, and from neighbouring countries [26]. The tropical climate and complex local meteorological conditions also affect the formation of secondary pollutants [27].…”
Section: Introductionmentioning
confidence: 99%